2015
DOI: 10.1002/jcb.25201
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblastic Synoviocytes Secrete Plasma Proteins Via α2‐Macroglobulins Serving as Intracellular and Extracellular Chaperones

Abstract: Changes in plasma protein levels in synovial fluid (SF) have been implicated in osteoarthritis and rheumatoid arthritis. It was previously thought that the presence of plasma proteins in SF reflected ultrafiltration or extravasation from the vasculature, possibly due to retraction of inflamed endothelial cells. Recent proteomic analyses have confirmed the abundant presence of plasma proteins in SF from control and arthritic patients. Systematic depletion of high-abundance plasma proteins from SF and conditione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Although A2M is a well-established extracellular chaperone capable of clearing misfolded, aggregated proteins including Aβ, recent evidence suggests that it may also function as an intracellular chaperone. 70 This finding, in combination with our results suggesting that A2M may respond to tau phsphorylation states, opens up a novel line of investigation to further study A2M-tau interactions in vivo . Our results additionally suggest the importance of better understanding mechanisms underlying the sex-specific A2M response in preclinical AD.…”
Section: Discussionsupporting
confidence: 71%
“…Although A2M is a well-established extracellular chaperone capable of clearing misfolded, aggregated proteins including Aβ, recent evidence suggests that it may also function as an intracellular chaperone. 70 This finding, in combination with our results suggesting that A2M may respond to tau phsphorylation states, opens up a novel line of investigation to further study A2M-tau interactions in vivo . Our results additionally suggest the importance of better understanding mechanisms underlying the sex-specific A2M response in preclinical AD.…”
Section: Discussionsupporting
confidence: 71%
“…The identified differential peptides cement the role of neuroendocrine and enteric nervous systems as measured via hormones, peptides, protein fragments, naturally occurring within the circulating plasma. The nature and context of these peptides in the enriched low mass fraction of plasma may be related to the associated increase in vascular permeability (35,36), as well as the activated binding and packaging of peptides into complexes in the endoplasmic reticulum (ER) tagged for secretion (37). At the interface between the epithelium and lymphatic/circulatory system, the altered secretion of lyzozyme, defensins, IgA and mucins as well as the catabolism and breakdown of (intracellular) proteins become sequestered into the circulatory system and can be indicators of disease, phenotype and severity.…”
Section: Discussionmentioning
confidence: 99%
“…Our data has shown increased levels of kininogen in IBD patients, along with other acute phase proteins such as fibrinogen, ␤-2-microglobulin, ␣-2-macroglobulin, haptoglobin and the apolipoproteins. In particular ␣-2-macroglobulin has previously been implicated as an intra and extracellular chaperone of vesicular traffic in the ER (37,38). All proteins and small peptides have been measured initially from the enriched low mass component of plasma as well as in unfractionated plasma and serum using MRM.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate validation of the gene expression findings was to prove that translation, biosynthesis and secretion of individual plasma proteins take place in HK2 cells. Newly synthesized secretory proteins in serum‐free cultured HK2 medium were directly evaluated by our sensitive non‐reducing Western blotting method [Zhao et al, ]. As PETC are polar cells similar to synoviocytes, any secretory protein synthesized will exit either from the apical side (lumen facing medium) or from the basolateral side (interstitial facing plastic side or two cells interacting each other) [Stoops and Caplan, ].…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that plasma proteins contained in the joint (synovial) fluid are not leaked from the circulation, but rather, are synthesized and secreted by the fibroblastic synoviocytes, polarized cells lining inside the synovium [Zhao et al, ]. This suggests that synoviocytes behave as hepatocytes in the production and secretion of plasma proteins into the synovial fluids.…”
mentioning
confidence: 99%